2018
DOI: 10.1016/j.phymed.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of cytotoxic compounds from the seeds of Euphorbia lathyris

Abstract: Analysis of the screening data compared with compound structures suggested that the substitutions at C-3, C-5, C-7, and C-15 are critical for cytotoxicity, as well as cell type-selectivity. Furthermore, results of cytotoxic mechanism analysis demonstrated for the first time that compounds 3 and 5 disrupted normal cell cycle progression, whereas compounds 2‒5 induced obvious actin filament aggregation, as well as partial interference of the microtubule network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…On the other hand, although some authors also used ethanol extraction from Euphorbia lathyris seeds, their methodologies are significantly different than ours in terms of ethanol concentration, pH, temperature, or extraction process. For instance, Teng et al [29] used 95% ethanol, obtaining a variety of compounds in the extract that significantly differ from those obtained with our methodology. In fact, these authors mainly obtained diterpenoids from the Latin-type seed (Euphorbia factors L1, L2, L3, L8, and L9), which were not present in our extract.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…On the other hand, although some authors also used ethanol extraction from Euphorbia lathyris seeds, their methodologies are significantly different than ours in terms of ethanol concentration, pH, temperature, or extraction process. For instance, Teng et al [29] used 95% ethanol, obtaining a variety of compounds in the extract that significantly differ from those obtained with our methodology. In fact, these authors mainly obtained diterpenoids from the Latin-type seed (Euphorbia factors L1, L2, L3, L8, and L9), which were not present in our extract.…”
Section: Discussionmentioning
confidence: 77%
“…Bicchi et al [ 27 ] described the presence of diterpenoid fractions corresponding to ingenol and Euphorbia factors in seed oil from Euphorbia lathyris , whereas Jiao et al [ 28 ] analyzed an ethanolic extract from seeds of Euphorbia lathyris and identified 22 types of compounds, including diterpenoids, triterpenoids, steroids, fatty acid esters, and coumarins. Moreover, Teng et al [ 29 ] obtained an ethanolic extract from seeds of Euphorbia lathyris using 95% ethanol under reflux and reported the existence of lathyran-type diterpenoids, highlighting five diterpenes with a lathyran structure (the Euphorbia factors L1, L2, L3, L8, and L9). These compounds showed cytotoxic activity against lung, nasopharyngeal, and breast (triple negative) carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…The seeds of Euphorbia lathyris are utilized as traditional Chinese medicine for treating terminal schistosomiasis, ascites, hydropsy, and snakebites . It is an abundant source of special diterpenoids with various macrocyclic and polycyclic skeletons including jatrophane, ningenane, daphnane, tigliane, and lathyrane .…”
Section: Introductionmentioning
confidence: 99%
“…[13] The seeds of Euphorbia lathyris are utilized as traditional Chinese medicine for treating terminal schistosomiasis, ascites, hydropsy, and snakebites. [14][15][16] It is an abundant source of special diterpenoids with various macrocyclic and polycyclic skeletons including jatrophane, ningenane, daphnane, tigliane, and lathyrane. [17,18] Some of these diterpenoids possess various biological activities, such as anticancer, [19,20] multidrug resistance (MDR) reversal, [21,22] antiviral, [23] and antifungal effects.…”
Section: Introductionmentioning
confidence: 99%
“…Euphorbia is a large genus of the Euphorbiaceae family that comprises more than 2000 species growing nearly in most climatic conditions all over the world [7]. Many favorable pharmacological properties have been identified for some Euphorbia species like antioxidant, anti-inflammatory, anticancer, and hepatoprotective effects [8,9,10]. Nonetheless, some hazardous impacts have been recognized for other species.…”
Section: Introductionmentioning
confidence: 99%